Polymer solid electrolyte and preparation method and application thereof

By using carboxyl and amine groups to neutralize monomers in the polymer solid electrolyte for acid-base, the crosslinked polymer is formed, and the problems of low ionic conductivity and insufficient mechanical strength in the prior art are solved, and the effects of high ionic conductivity, excellent mechanical properties and long cycle life are achieved.

CN119764544AActive Publication Date: 2025-04-04CHONGQING TALENT NEW ENERGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411968011.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing polymer solid electrolytes have problems such as low ion conductivity, low lithium ion migration number and low mechanical strength. The composite doped inorganic electrolytes have problems such as uneven dispersion and easy agglomeration, which cannot effectively increase the number of lithium ion migration.

Method used

By using carboxyl group-containing monomers and amine group-containing monomers to neutralize acid-base, forming a positively charged group, which is conducive to the migration of lithium ions, forming a first crosslinked polymer with a three-dimensional network structure, and improving ionic conductivity and mechanical properties.

Benefits of technology

It achieves higher ionic conductivity, higher tensile strength and excellent flexibility, improves lithium ion migration number and electrochemical stability, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_11
    Figure SMS_11
  • Figure SMS_12
    Figure SMS_12
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state batteries, in particular to a polymer solid-state electrolyte and a preparation method and application thereof. The polymer solid electrolyte comprises a first cross-linked polymer, a polymer electrolyte and a lithium salt, and the first cross-linked polymer is generated by reaction of a first monomer and a second monomer; the first monomer contains one or more carboxyl groups, and the second monomer contains one or more amino groups. According to the invention, a monomer containing carboxyl and a monomer containing amido are subjected to acid-base neutralization to form a positively charged group which is beneficial to migration of lithium ions, and carboxylate ions and the positively charged group in a basic group interact and are connected together to form a three-dimensional network structure; the generated first cross-linked polymer has higher ionic conductivity, higher tensile strength, excellent flexibility and other properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a polymer solid-state electrolyte and a preparation method and application thereof. Background Art

[0002] Commercial lithium-ion batteries mainly use organic liquid electrolytes, which are prone to short circuits, leakage, and flammability. Using solid electrolytes instead is one of the effective means to solve the problem. Inorganic solid electrolytes have poor processability and flexibility, which limits their commercial application. Although polymer solid electrolytes represented by polyethylene oxide (PEO) and polyvinylidene fluoride (PVDF) have advantages, PEO polymer solid electrolytes have disadvantages such as low room temperature ionic conductivity, low lithium ion migration number, and low mechanical strength. Compounding and doping inorganic electrolytes in polymer electrolytes has problems such as uneven dispersion and easy agglomeration, and it cannot effectively increase the lithium ion migration number.

[0003] Therefore, it is urgent to develop a polymer electrolyte with high ionic conductivity, lithium ion transference number and good mechanical properties. Summary of the invention

[0004] In order to solve the above-mentioned problems in the prior art, the present invention provides a polymer solid electrolyte and a preparation method and application thereof, which has higher ionic conductivity, tensile strength, excellent flexibility and other properties.

[0005] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a polymer solid electrolyte, which includes a first cross-linked polymer, a polymer electrolyte and a lithium salt, wherein the first cross-linked polymer is generated by reacting a first monomer with a second monomer; the first monomer contains one or more carboxyl groups, and the second monomer contains one or more amino groups.

[0006] The present invention finds that acid-base neutralization is performed by using a monomer containing a carboxyl group and a monomer containing an amine group, wherein hydrogen ions are dissociated from the carboxyl group -COOH in the first monomer to form carboxylate ions -COO-, and the basic group amine group in the second monomer captures hydrogen ions to form positively charged groups, which is beneficial to the migration of lithium ions, and the carboxylate ions and the positively charged groups in the basic groups interact and connect together to form cross-linking points, and multiple carboxyl groups can react with multiple amine functional groups to form a three-dimensional network structure to generate a first cross-linked polymer; the first cross-linked polymer has higher ionic conductivity, higher tensile strength, excellent flexibility and other properties.

[0007] Preferably, the first monomer has the following general structural formula: ; R represents C1~C 10alkyl, hydroxyl or carboxyl, or a group consisting of the above groups; n1 represents any integer from 1 to 100.

[0008] More preferably, R represents a C1-C3 alkyl group, a hydroxyl group or a carboxyl group; and n1 represents any integer from 20 to 60.

[0009] The present invention finds that when the first monomer is of the above general formula, a more stable polymer network structure can be formed with good tensile strength and toughness. In addition, when the monomer chain length is within the above range, a polymer electrolyte with a suitable molecular chain length can be formed, providing an effective transmission channel for ions and improving ion mobility. When the molecular chain length is appropriate, the polymer electrolyte can better resist the destruction of its structure by redox reactions during the battery charging and discharging process, thereby facilitating the improvement of the electrochemical stability of the polymer electrolyte.

[0010] As some embodiments of the present invention, the value of n1 in the first monomer can be any value among 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 or a numerical range with any two of them as endpoints.

[0011] Preferably, the second monomer comprises: , and n2~n4 are independently, identically or differently represented by any integer in the range of 1~100.

[0012] More preferably, n2-n4 each independently, identically or differently represent any integer from 10-30.

[0013] More preferably, the second monomer is and / or .

[0014] As some embodiments of the present invention, the values ​​of n2~n4 in the second monomer can be independently, the same or different and can be any value of 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 or a numerical range with any two of them as endpoints.

[0015] In the structural formula of the first monomer and the second monomer, the smaller the value of n1~n4 is within the selected range, the lower the molecular weight is and the fewer the cross-linking points are, resulting in lower strength of the first cross-linked polymer formed therefrom; and the larger the value of n1~n4 is, the higher the molecular weight is and the more cross-linking points are, resulting in higher strength of the first cross-linked polymer formed therefrom, but reduced ductility and flexibility.

[0016] In the present invention, the first monomer and the second monomer are added in a mass ratio, and the difference in the amount relationship between the two will result in different cross-linking degrees, so the tensile strength of the polymer film and the mechanical strength of the film will also become adjustable.

[0017] Preferably, the mass ratio of the first monomer to the second monomer is 1:(0.1-5); preferably, the mass ratio of the first monomer to the second monomer is 1:(1-3).

[0018] The present invention finds that when the amount relationship between the first monomer and the second monomer in the first cross-linked polymer is within the above range, all carboxyl groups of the diacid can be almost completely neutralized, and the formed polymer electrolyte has a relatively regular ionic structure, which can provide a stable ion channel during ion transmission, and has relatively balanced mechanical properties. It is neither too soft due to excessive acidic unreacted parts, nor too brittle due to excessive neutralization. For battery performance, within the above range, the lithium salt is evenly distributed in the polymer electrolyte, and the ions can be stably transmitted along the channels formed between the polymer chains, thereby obtaining a relatively high ionic conductivity. Stable ion conduction can ensure that during the charge and discharge process, a sufficient amount of lithium ions can shuttle back and forth between the positive and negative electrodes, so that the battery can reach the designed capacity. In addition, this regular structure helps to maintain the stability of battery performance, thereby extending the cycle life of the battery.

[0019] Preferably, the polymer electrolyte includes one or more of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-chlorotrifluoroethylene, polytetrafluoroethylene, polyacrylonitrile, polymethyl methacrylate, polypropylene carbonate, polyphenylene sulfide, polyethyl cyanoacrylate, polypentylene succinate, polyvinyl chloride, polyacrylic acid, polyvinyl carbonate, polyvinyl butyral, polyvinyl pyrrolidone, polyimide, polyacrylate, polyurethane, nitrile rubber, styrene-butadiene rubber and carboxymethyl cellulose.

[0020] Preferably, when the ratio of the mass of the polymer electrolyte to the total mass of the first monomer and the second monomer is 1:(0.5-3), it can provide sufficient ion transport channels while having good mechanical properties, certain mechanical strength and flexibility, and ensuring good electrochemical stability.

[0021] Preferably, the lithium salt includes one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate and lithium nitrate.

[0022] Preferably, based on the total mass of the polymer electrolyte, the first monomer, the second monomer and the lithium salt, the amount of the lithium salt is 10 wt % to 40 wt %.

[0023] In the present invention, the polymer solid electrolyte may also contain inorganic materials. The inorganic material includes inorganic solid electrolyte and / or inorganic ceramic; the inorganic solid electrolyte includes one or more of oxide solid electrolyte, sulfide solid electrolyte, halide solid electrolyte, borate solid electrolyte and nitride solid electrolyte. The inorganic solid electrolyte is an oxide solid electrolyte. The oxide solid electrolyte includes one or more of perovskite oxide solid electrolyte, garnet oxide solid electrolyte and NASICON oxide solid electrolyte. The perovskite oxide solid electrolyte is selected from lithium lanthanum titanium oxide; the garnet oxide solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, niobium-doped lithium lanthanum zirconium oxide, tantalum-doped lithium lanthanum zirconium oxide and niobium-tantalum dual-doped lithium lanthanum zirconium oxide; the NASICON oxide solid electrolyte is selected from one or more of lithium aluminum titanium phosphate, lithium yttrium titanium phosphate and lithium aluminum germanium phosphate. The inorganic ceramic includes one or more of nitride, carbide, metal oxide and non-metal oxide. The nitride is selected from one or more of silicon nitride, titanium nitride, aluminum nitride, boron nitride, and magnesium nitride; the carbide is selected from one or more of silicon carbide and boron carbide; the metal oxide is selected from one or more of aluminum oxide, titanium dioxide, zirconium dioxide, and magnesium oxide; the non-metallic oxide is selected from one or more of silicon dioxide and boron oxide.

[0024] Preferably, based on the total mass of the system (excluding solvent), the amount of the inorganic material is 20-40 wt %.

[0025] In a second aspect, the present invention provides a method for preparing the polymer solid electrolyte, comprising the following steps: S1, stirring and mixing the lithium salt, polymer electrolyte and organic solvent until they are completely dissolved to obtain a mixed solution A; S2, mixing the first monomer, the second monomer, the initiator and the mixed solution A to obtain a polymer solid electrolyte slurry; S3. Apply the polymer solid electrolyte slurry on the substrate with a scraper, and obtain the polymer solid electrolyte after drying.

[0026] Preferably, in S1, the mixing temperature is 35-45°C; Preferably, in S2, the mixing temperature is 35-45°C; Preferably, in S3, the drying temperature is 65-75°C.

[0027] As a preferred embodiment of the present invention, the method for preparing the polymer solid electrolyte comprises the following steps: S1. Stir and mix the lithium salt, polymer electrolyte and organic solvent at 35-45° C. until they are completely dissolved to obtain a mixed solution A; S2, mixing the first monomer, the second monomer, the initiator and the mixed solution A, and stirring at 35-45° C. for 4-6 hours to obtain a polymer solid electrolyte slurry; S3. Coat the polymer solid electrolyte slurry on the substrate with a scraper, and vacuum dry it at 65-75° C. for 18-24 h to obtain a polymer solid electrolyte.

[0028] Preferably, the initiator comprises azobisisobutyronitrile; more preferably, based on the total mass of the first monomer and the second monomer, the amount of the initiator is 0.5 wt % to 2 wt %.

[0029] Preferably, the organic solvent includes one or more of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.

[0030] As a preferred embodiment of the present invention, the method for preparing the polymer solid electrolyte comprises the following steps: S1. Stir and mix LiTFSI, PVDF and DMF at 35-45° C. until they are completely dissolved to obtain a mixed solution A.

[0031] S2, mixing the first monomer, the second monomer, azobisisobutyronitrile and the mixed solution A, stirring at 35-45° C. for 4-6 hours to obtain a polymer solid electrolyte slurry; S3. Coat the polymer solid electrolyte slurry on the substrate with a scraper, and vacuum dry it at 65-75° C. for 18-24 h to obtain a polymer solid electrolyte.

[0032] In the present invention, those skilled in the art can also pour the polymer solid electrolyte slurry onto a substrate, and obtain a polymer solid electrolyte membrane after drying; the substrate can be a supporting plate such as a glass plate.

[0033] In a third aspect, the present invention provides a solid-state battery comprising the polymer solid electrolyte.

[0034] The polymer solid electrolyte provided by the present invention and its preparation method and application, by using carboxyl-containing monomers and amine-containing monomers for acid-base neutralization to form positively charged groups, which are beneficial to the migration of lithium ions, and the carboxylate ions and the positively charged groups in the alkaline groups interact and connect together to form a three-dimensional network structure, and the generated first cross-linked polymer has higher ionic conductivity, higher tensile strength, excellent flexibility and other properties. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.

[0037] Example 1 This embodiment provides a polymer solid electrolyte, and the preparation method thereof comprises the following steps: S1. 3 g of LiTFSI, 3 g of PVDF and 30 g of DMF were stirred and mixed at 40° C. until they were completely dissolved to obtain a mixed solution A.

[0038] S2, adding 1 g of the first monomer, 2 g of the second monomer, and 0.03 g of azobisisobutyronitrile to the mixed solution A, stirring at 40° C. for 6 h to obtain a polymer solid electrolyte slurry; S3. Coat the polymer solid electrolyte slurry on a glass plate with a scraper, and vacuum dry at 70° C. for 18 to 24 hours to obtain a polymer solid electrolyte.

[0039] The first monomer is , R=-CH3, n1=20, the second monomer is , n2=10.

[0040] Example 2 This embodiment provides a polymer solid electrolyte, and the preparation method thereof is different from that of Embodiment 1 only in that: in the first monomer, R is -CH3, n1=30, and in the second monomer, n2=10.

[0041] Example 3 This embodiment provides a polymer solid electrolyte, and the preparation method thereof is different from that of Embodiment 1 only in that: in the first monomer, R is -CH3, n1=40, and in the second monomer, n2=10.

[0042] Example 4 This embodiment provides a polymer solid electrolyte, and the preparation method thereof is different from that of Embodiment 1 only in that: in the first monomer, R is -CH3, n1=20, and in the second monomer, n2=20.

[0043] Example 5 This embodiment provides a polymer solid electrolyte, and the preparation method thereof is different from that of Embodiment 1 only in that: in the first monomer, R is -CH3, n1=30, and in the second monomer, n2=30.

[0044] Example 6 This embodiment provides a polymer solid electrolyte, and the preparation method thereof is different from that of embodiment 1 only in that: the second monomer is , in the second monomer, n3=10.

[0045] Example 7 This embodiment provides a polymer solid electrolyte, and the preparation method thereof is different from that of Embodiment 1 only in that the mass ratio of the first monomer to the second monomer is 1:1.

[0046] Example 8 This embodiment provides a polymer solid electrolyte, and the preparation method thereof is different from that of Embodiment 1 only in that the mass ratio of the first monomer to the second monomer is 1:3.

[0047] Example 9 This embodiment provides a polymer solid electrolyte, and the preparation method thereof is different from that of Embodiment 1 only in that the mass ratio of the first monomer to the second monomer is 1:6.

[0048] Example 10 This embodiment provides a polymer solid electrolyte, and the preparation method thereof comprises the following steps: S1. 2 g of LiFSI, 4 g of PEO and 30 g of NMP were stirred and mixed at 40° C. until they were completely dissolved to obtain a mixed solution A.

[0049] S2, adding 1 g of the first monomer used in Example 1, 2 g of the second monomer used in Example 1, and 0.03 g of azobisisobutyronitrile to the mixed solution A, and stirring at 40° C. for 6 h to obtain a polymer solid electrolyte slurry; S3. Coat the polymer solid electrolyte slurry on a glass plate with a scraper, and vacuum dry at 70° C. for 18 to 24 hours to obtain a polymer solid electrolyte.

[0050] Comparative Example 1 This comparative example provides a polymer solid electrolyte, and the preparation method thereof is different from that of Example 1 only in that the first monomer is an equal amount of phytic acid.

[0051] Test example 1. The properties of the polymer electrolyte membranes prepared in the examples and comparative examples were tested, and the results are shown in Table 1.

[0052] Test methods include: Conductivity test method: The polymer electrolyte was cut into a membrane with a diameter of 16.5 mm, and then placed between two steel sheets. The resistance was tested by AC impedance using an electrochemical workstation at a temperature of 30°C and a frequency range of 10 -2 ~10 -6 Hz, the AC voltage is 10mV, and then the ionic conductivity is calculated by the following formula; the calculation formula is: σ=L / R×S; where σ is the ionic conductivity (S / cm), L is the thickness of the electrolyte membrane (cm), R is the volume resistance of the membrane (Ω), and S is the electrode area (cm 2 ).

[0053] Lithium ion migration number test method: The combination of constant potential DC polarization and EIS test is used to evaluate the lithium ion migration number of polymer electrolytes. After the lithium sheet electrode is used as the working electrode and the counter electrode, the test cell is assembled in the glove box, and the electrolyte constant current DC polarization curve (it curve) and the electrochemical impedance spectrum before and after polarization are tested at room temperature in an electrochemical workstation, and then according to the formula: , calculate the lithium ion migration number, where ΔV is the polarization voltage, I0 and I s are the initial current and stable current obtained from the DC polarization test, R0 and R s The interfacial resistance of the polymer electrolyte before and after DC polarization test is shown in Figure 2. The DC polarization time is 7200 s and the applied polarization voltage is 10 mV.

[0054] Oxidation potential test method: The electrochemical stability window of the solid polymer electrolyte was measured by linear sweep voltammetry (LSV). A stainless steel inert electrode was used as the working electrode, and a lithium sheet was used as the reference electrode. After the test cell was assembled in a glove box, the test was performed in an electrochemical workstation at room temperature, with a scan range of 2~6V and a scan rate of 1 mV / s.

[0055] Tensile strength test method: Test in accordance with national standard GB / T 1040-1992.

[0056] Elongation test method: Test in accordance with national standard GB / T 1040-1992.

[0057] Table 1

[0058] 2. The present invention further provides a battery assembled using the above polymer solid electrolyte, and tests its cycle performance. The test results are shown in Table 2.

[0059] The preparation method comprises: assembling CR2032 button cells in a glove box filled with argon, wherein the positive electrode material is a nickel-cobalt-manganese ternary (NCM811) material, the negative electrode is a metal lithium sheet, the electrolyte is the polymer electrolyte prepared in Examples 1 to 9 and Comparative Example 1, and the battery capacity is about 1 mAh.

[0060] Cycle test method: The battery was allowed to stand for 10 hours before testing on a blue power test system. The battery was cycled at a charge / discharge rate of 0.2 / 1C at 25°C using a constant current constant voltage charge / constant current discharge (CCCV / DC) mode with charge and discharge cut-off voltages of 4.2V and 2.7V, respectively. The cut-off current of the constant potential was 0.05C. The battery was allowed to stand for 10 minutes between each cycle of charge and discharge.

[0061] Table 2

[0062] Comparing Examples 7 to 9 with Example 1, it can be seen that under the same conditions, the mass ratio of the first monomer and the second monomer will significantly affect the performance of the polymer electrolyte membrane and the performance of the battery. Specifically, when the amount relationship of the first monomer and the second monomer is within the limited range of the present invention, the polymer electrolyte membrane has higher ionic conductivity, higher tensile strength and excellent flexibility and other properties, and at the same time, the cycle performance of the battery is better. Comparing Example 10 with Example 1, it can be seen that in addition to the selection of the first monomer and the second monomer, the selection of lithium salts, polymer electrolytes, organic solvents and initiators in the system will also affect the performance of the polymer electrolyte membrane and the performance of the battery to a certain extent. Comparing Example 1 with Comparative Example 1, it can be seen that under the same conditions, after the selected diacid is replaced with phytic acid, due to the presence of multiple phosphate groups and complex structure of phytic acid, the steric hindrance is large, and the acid-base neutralization cross-linking reaction activity is relatively low. In addition, due to the mutual influence between the phosphate groups and the complex combination mode with the polymer chain, it is easy to cause uneven cross-linking, affecting the mechanical properties and stability of the polymer, and the test results show lower ionic conductivity, low tensile strength and poor cycle stability.

[0063] Meanwhile, experiments have shown that when the first monomer contains ethyl, propyl, hydroxyl or carboxyl, the performance of the prepared polymer electrolyte membrane and the battery are comparable to those of Example 1, which will not be further elaborated here.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polymer solid electrolyte, characterized in that: It includes a first cross-linked polymer, a polymer electrolyte and a lithium salt, wherein the first cross-linked polymer is generated by reacting a first monomer with a second monomer; The first monomer contains one or more carboxyl groups, and the second monomer contains one or more amino groups.

2. The polymer solid electrolyte according to claim 1, characterized in that The first monomer has the following general structural formula: ; R represents C1~C 10 alkyl, hydroxyl or carboxyl, or a group consisting of the above groups; n1 represents any integer from 1 to 100.

3. The polymer solid electrolyte according to claim 1, characterized in that: The second monomer comprises: , and n2~n4 are independently, identically or differently represented by any integer in the range of 1~100.

4. The polymer solid electrolyte according to any one of claims 1 to 3, characterized in that The mass ratio of the first monomer to the second monomer is 1:(0.1-10); preferably, the mass ratio of the first monomer to the second monomer is 1:(1-3).

5. The polymer solid electrolyte according to any one of claims 1 to 4, characterized in that The polymer electrolyte comprises one or more of polyethylene oxide, polyvinylidene fluoride, polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-chlorotrifluoroethylene, polytetrafluoroethylene, polyacrylonitrile, polymethyl methacrylate, polypropylene carbonate, polyphenylene sulfide, polyethyl cyanoacrylate, polypentylene succinate, polyvinyl chloride, polyacrylic acid, polyvinyl carbonate, polyvinyl butyral, polyvinyl pyrrolidone, polyimide, polyacrylate, polyurethane, nitrile rubber, styrene-butadiene rubber and carboxymethyl cellulose; Preferably, the ratio of the mass of the polymer electrolyte to the total mass of the first monomer and the second monomer is 1:(0.5-3).

6. The polymer solid electrolyte according to any one of claims 1 to 5, characterized in that The lithium salt includes one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate and lithium nitrate; preferably, based on the total mass of the polymer electrolyte, the first monomer, the second monomer and the lithium salt, the amount of the lithium salt is 10wt%~40wt%.

7. The method for preparing a polymer solid electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, stirring and mixing the lithium salt, polymer electrolyte and organic solvent until they are completely dissolved to obtain a mixed solution A; S2, mixing the first monomer, the second monomer, the initiator and the mixed solution A to obtain a polymer solid electrolyte slurry; S3, coating the polymer solid electrolyte slurry on the substrate with a scraper, and obtaining the polymer solid electrolyte after drying; Preferably, in S1, the mixing temperature is 35-45°C; Preferably, in S2, the mixing temperature is 35-45°C; Preferably, in S3, the drying temperature is 65-75°C.

8. The preparation method according to claim 7, characterized in that: The initiator includes azobisisobutyronitrile; preferably, based on the total mass of the first monomer and the second monomer, the amount of the initiator is 0.5wt% to 2wt%.

9. The polymer solid electrolyte according to claim 7 or 8, characterized in that: The organic solvent includes one or more of dimethyl sulfoxide, N,N-dimethylformamide and N-methylpyrrolidone.

10. A solid-state battery, characterized in that: It comprises the polymer solid electrolyte described in any one of claims 1 to 6 or the polymer solid electrolyte prepared by the preparation method described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Polymer electrolyte, preparation method thereof and lithium battery

    CN117996177A

  • Quasi-solid polymer electrolyte membrane based on cellulose main body as well as preparation method and application of quasi-solid polymer electrolyte membrane

    CN118589033A

  • Manufacture of polymeric solid electrolyte, polymeric solid electrolyte, and electrochemical device

    JP2001043896A

  • Composite for solid polyelectrolyte

    JP2004213940A

  • Polysiloxane-polyolefin complex gel electrolyte, and lithium battery using the same

    JP2005285377A